Risk Factors Affecting Health of Modern Specialists in Vocational and Psychological Training - Tverdokhliebova, Natalia; Yevtushenko Nataliіa (Освітні виклики, 2023)
The health of people in Ukraine has become particularly relevant in recent years, as Ukrainian society is exposed to unprecedented external threats, such as the war with Russia, that negatively affect plans, goals and quality of life, and the increases psychological tensions that lead to the deterioration of people’s physical, mental and social health. This also applies eqully to participants in the educational environment. Today, in light of the military actions in Ukraine, it is necessary in higher educational institutions to address new and non-standard tasks challenge students’ health and their personal resources in the process of education. A complex combination of new and unpredictable challenges and risks resulting from challenges to the socio-political situation in the country such as the Covid pandemic, the war with Russia, and the growing presence of digital technologies in the educational space, actualizes the deployment of a series of studies about risk factors affecting students’ health. The purpose of this article is to study the particular risk factors affecting the health status of today’s students distinctive in order to help develop a better system of protective measures to prevent morbidity in the process of their education. The methodology in this article is based on the fundamental methodological principles of consistency and interdisciplinary approach and includes the use of a collection of general scientific (explanation, comparison, classification, generalization, systematization) and empirical (observation, conversation, description, analysis, experiment) methods. Based upon these, we have formulated a set of practical recommendations for providing appropriate conditions for maintaining students’ health in modern learning conditions. Within the framework of our study, the following results were achieved: the views of scientists on the definition of factors affecting the level of youth health were summarized; the risk factors influencing the health indicators of students are considered; the results of a study about the prevalence of diseases among students in a special medical group from the National Technical University "Kharkiv Polytechnic Institute" are given, the recommendations are formulated for the prevention of morbidity among students in higher educational institutions in the process of vocational training in war conditions. The conclusions allow us to state that in order to preserve the health of modern specialists in current conditions, it is necessary to identify the main groups of risk factors, understand the mechanisms of their action to a specialist and apply timely appropriate measures and techniques to prevent them, depending on the current situation.